Mecanismos moleculares envolvidos na apoptose induzida pelo vírus da cinomose canina in vivo e in vitro - Helen Lima Del Puerto (2010)
Canine distemper (CD) is an immunosuppressive disease caused by the canine distemper virus (CDV). Pathogenesis includes mainly complications in the CNS and immunosuppression that are not completely understood. Dogs naturally infected with CDV show apoptotic cells in lymphoid tissues and cerebellum, but the apoptotic mechanism is not well characterized. Thus, in this study we evaluated the expression of Bax, Bcl-2, Caspases 3, -8 and -9 mRNA in the peripheral blood, lymph nodes and cerebellum of CDV infected (CDV+) and non-infected (CDV-) dogs by real-time PCR. Blood samples from 12 CDV+ and 8 CDV- dogs, diagnosed by RT-PCR, were used for hematological analysis and to evaluate apoptotic gene expression using real-time PCR. Cerebellum and lymph nodes of 4 CDV+ and 3 CDV- dogs were also used in real-time PCR. No significant differences were statistically found in the expressions of Caspase 3, -8, -9, Bax and Bcl-2 mRNA or in the hematological results between CDV+ and CDV- dogs. Expressions of Bax, Caspase 3, -8 and -9 was significantly higher (p<0.05) in CDV+ cerebellum compared to CDV- dogs. In addition, expressions of Caspase 3 and -8 were significantly higher (p<0.05) in the lymph nodes of CDV+ compared to CDV- dogs. These findings suggest that CDV induces apoptosis in the cerebellum and lymph nodes in different ways. Lymph node apoptosis might occur via Caspase 3 activation, through the Caspase 8 pathways, and cerebellum apoptosis might occur via Caspase 3 activation, through Caspase 8 and through the mitochondrial pathway.